2015
DOI: 10.1016/j.ecoenv.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Detection and diversity of aeromonads from treated wastewater and fish inhabiting effluent and downstream waters

Abstract: a b s t r a c tA two-season investigation of the wastewater treatment plant (WWTP) effluent, of related waters, sludge and fish across a wide area and 11 stations, with emphasis on Aeromonas spp. was conducted. Aeromonas veronii was the prevailing aeromonad isolated by MALDI TOF MS in the summer period. A rise of Aeromonas hydrophila was observed in summer in raw sewage, treated wastewater and effluent-carrying canal. The ratio of aeromonad species retrieved from fish tissues did not correspond with the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
3
13
1
Order By: Relevance
“…Indeed, such Aeromonas species could be well adapted to a estuarine environment having a cooler surface water with mean temperature of 13.4°C (min: 5.3°C/ max 21.3°C). Except for A. salmonicida (Henriques et al, 2006), these species, previously observed in farmed fishes (water and fish) (Esteve et al, 1995; Schmidt et al, 2001; Hatha et al, 2005; Behbahani et al, 2014; Bartkova et al, 2016) and in waste water (Figueira et al, 2011; Marti and Balcázar, 2015; Popovic et al, 2015; Vaz-Moreira et al, 2015; Varela et al, 2016), have never been, as far as we know, described in coastal and anthropized estuary waters. Only the species A. hydrophila , A. caviae , A. sobria , and A. veronii have been reported in coastal or estuarine environments (the Adriatic Sea, Italy) (Dumontet et al, 1996; Fiorentini et al, 1998; Gugliandolo et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, such Aeromonas species could be well adapted to a estuarine environment having a cooler surface water with mean temperature of 13.4°C (min: 5.3°C/ max 21.3°C). Except for A. salmonicida (Henriques et al, 2006), these species, previously observed in farmed fishes (water and fish) (Esteve et al, 1995; Schmidt et al, 2001; Hatha et al, 2005; Behbahani et al, 2014; Bartkova et al, 2016) and in waste water (Figueira et al, 2011; Marti and Balcázar, 2015; Popovic et al, 2015; Vaz-Moreira et al, 2015; Varela et al, 2016), have never been, as far as we know, described in coastal and anthropized estuary waters. Only the species A. hydrophila , A. caviae , A. sobria , and A. veronii have been reported in coastal or estuarine environments (the Adriatic Sea, Italy) (Dumontet et al, 1996; Fiorentini et al, 1998; Gugliandolo et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…was conducted. They found that a rise of A. hydrophila was observed in summer in raw sewage, treated wastewater, and effluent-carrying canal [29]. The removal efficiency of microbial contaminants was evaluated from a local wastewater treatment plant and highlighted the potential risk associated with wastewater reuse for agricultural irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies clearly demonstrate the usefulness of rapid discrimination of environmental and particularly aquatic bacteria, mostly Vibrio and Aeromonas strains (Donohue et al, 2007;Benagli et al, 2012;Eddabra et al, 2012, Schirmeister et al, 2014Topić Popović et al, 2015). Koubek et al (2012) recommend whole-cell MALDI-TOF MS over 16S rRNA for rapid screening and discrimination of various environmental bacterial isolates.…”
Section: Maldi-tof Ms Applicability For Environmental Isolates (Watermentioning
confidence: 99%